The power of women's and men's Social Networks to catalyse normative and behavioural change: evaluation of an intervention addressing Unmet need for Family Planning in Benin - Theresa Y. Kim; Susan Igras; Kathryn M. Barker; Mariam Diakité; Rebecka I. Lundgren (BMC, 2022)
Plain English Summary In many places with relatively low family planning use, insufficient program attention is paid to socio-normative barriers that influence need and method use. TJ catalyses women and men's social networks to spread new ideas and break communication and other social barriers that prevent women and men with unmet needs - people who wish to space their next birth but are not using effective family planning methods - from acting on their desires. A rigorous evaluation of the approach in rural Benin showed after only 14 months, TJ led to statistically significant improvements in intention to use contraception and met need. While showing substantial gains, women's use of contraception was not statistically significant. TJ increased women's and men's partner and network communication on fertility desires and family planning use and individual self-efficacy and confidence to act on intentions to address unmet need. The network influence on family planning use was equally significant. TJ led to new ideas within communities/social networks, including the perception that one's social networks approve of FP. Women and men who report that their network approves of FP were significantly more likely to discuss method use with their partners and seek services. TJ led to new perceptions that one's networks support FP. TJ represents an underused strategy for social and behaviour change. The social network approach encourages addressing the often-neglected social factors that stop women and men from acting on their desires to space births and use modern family planning methods.